The Political Dimension of Prophethood on Civilizing the Moral Ethics, Justice, and Class Reform - Abbas, Afifi Fauzi; Afifi, Abdullah A; Eliza, Mona; Muhammad, Adamu Abubakar (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2025)
This paper highlights the political dimension of Muhammad’s Prophethood as a comprehensive civilizational project aimed at improving moral ethics, justice, and class reform in the framework of society leadership and governance. Using a conceptual–narrative approach that draws from classical Islamic historiography (Sirah Nabawiyah) and modern interpretive context, the study situates the Prophet’s mission as both a spiritual awakening and a political transformation grounded in tauhid (divine unity). The research argues that the Prophet redefined politics as an ethical mission, transforming it from an arena of domination into a means of cultivating justice and moral consciousness. The Meccan phase illustrates moral resistance and class awakening, where faith became a force of ethical protest against social oppression. The Hijrah to Medina marked a transition from moral resistance to institutional civilization, establishing the Charter of Medina as one of the earliest constitutional models of pluralistic justice. Within the Madinan foundation, the Prophet institutionalized justice, social economy instruments of moral ethics governance, creating a balance between spirituality, law, and civic duty. The study concludes that Prophet Muhammad’s leadership civilized politics by linking power to moral purpose and embedding ethics in governance, economy, and society. His vision of a madani (civilized) community presents an enduring model of ethical statecraft where human dignity, equality, and compassion guide public order. This synthesis of faith and justice demonstrates that the foundation of Islamic civilization is moral ethics based, not material, anchored in the pursuit of righteousness, social welfare, and universal peace.